On-Ground Processing for Spectral Efficiency Improvement in Next Generation Satellite Communications - Arnau, Jesus (Universidade de Vigo, 2014)
The eternal demand of improved spectrum exploitation for next generation satellite communications requires the study of techniques that are potentially able of a breakthrough. In this thesis we focus on two of the main issues hindering the performance of satellite communications.   In the first part of the thesis, we study the use of multi-user detection techniques in the return link of multibeam satellite systems operated with an aggressive frequency reuse strategy. We start by comparing their performance with respect to a traditional scenario, and study the possibility of splitting the processing between the gateway and the satellite to cope with practical constraints. We then study the fundamental performance limits of such a system when spatially correlated rain attenuation affects the users; analytical expressions are obtained for the high and low SNR regimes. Finally, we consider non perfect channel state information and obtain, through random matrix theory, an approximation of the residual error as a function of the system's parameters.   In the second part, we focus on link adaptation for mobile satellite communications. For the return link, we investigate the potential of open-loop channel state information, which is timely but scarcely accurate; the finding that this information is better than the traditional closed-loop one depending on the channel conditions motivated the study of an adaptive algorithm to dynamically balance both. Finally, in the forward link we considered the case where retransmissions are available, and designed the optimum modulation and coding scheme sequence for the different retransmissions of a packet in terms of throughput.
Keywords: satcom